Activation of caspase-3 pathway by expression of sGαi2 protein in BHK cells. - López-Aranda, Manuel Francisco; Navarro-Lobato, Irene; López-Téllez, Juan Félix; Blanco-Calvo, Eduardo; Masmudi-Martín, Mariam; Khan, Zafaruddin (Elsevier, 2008)
Treatment with dopamine and other dopamine D2 receptor agonists has been shown to induce cell death through activation of caspase-3 pathway. However, initial step that leads to the activation of caspase-3 in D2 receptor-mediated apoptotic pathway remains unclear. Recently, it was shown that a spliced variant of God2 protein (sG alpha i2) forms intracellular complex with D2 receptors by protein-protein interaction and that D2 drugs treatment causes the liberation of sG alpha i2 protein from complex. Now, we show that the unbound form of sG alpha i2 protein is able to activate caspase-3 pathway in baby hamster kidney (BHK) cells. Expression of sG alpha i2 protein in BHK cells led to the production of active form of caspase-3 and activation of p38 mitogen-activated protein kinase (1)38 MAPK) and extracellular regulated kinase 1/2 (ERK1/2). Co-expression of sG(xi2 with either D2 short (D2S) or D2 long (D2L) isoforms of dopamine D2 receptors blocked the activation of caspase-3 pathway. Thus, our results demonstrate that high level of unbound sG alpha i2 protein can affect the cell survival and engagement of this protein with D2 receptors can block this process. It is suggested that this process may be a crucial step in the initiation of D2 receptor-mediated cellular apoptosis through this pathway.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/16551
Keywords: Receptores de dopamina; Apoptosis; D2 receptor; ERK1/2; p38 MAPK; G i2 protein; Caspase